A constituição do sujeito no âmbito do desenvolvimento tecnológico : identidade do pequeno produtor ou formação discursiva? - Mendes, Luciano (2006)
We aimed, in this paper, to understand the influence of the program technological development called "Arenito Nova Fronteira" in the construction process, destruction or maintenance in the identity of the small rural producers in Umuarama-PR area. However, we accomplished a study about the identity in the several authors' perspective, in the philosophical, sociological and psychological contexts, with the intention of extracting the presuppositions that guide those fields. Besides this course, we also discussed about the small property in Brazil, in the intention of understanding their problems. Focusing the identity, for the considerations of the destruction process, we also shimmered the powder-modern critical studies on that thematic one. Those made us wondering if we could really speak about an identity of the small rural producers, because in spite of the discussions about identity to shimmer the identity as something subjective to the individual, we observed that is the social context that makes possible your existence. That discussion made us to look for to understand, in that way, two contexts: the subjective and the objective. Thus, we worked with the interview of life history, because the identity touches in aspects as the subject's continuity in the social context. It was with that vast theoretical and methodological discussion that we accomplished the interviews in life history with five small rural producers from Umuarama area. We observed that the construction process, destruction or maintenance of the identity, is a process that obeys the social designations and not the own subject. Being like this, we concluded that is not possible to speak from an own identity to the small rural producers, because the technological and marketing systems undermine with a supposed subjectivity of the subject.